YAJNA SRADDHA DAN YAJNA MEMUKUR - Rita Istari (Berkala Arkeologi, 2010)
The most popular text from Majapahit Era, Nagarakertagama, mentioned a ceremony called Yajna Sraddha. This ceremony is related to the dead. The description on the ceremony recalls to the present day Yajfia Memukur ceremony which is still conducted by Hindu Balinese. The purpose of Yajfia Sraddha and Yajfia Memukur ceremonies are basically similar. It is devoted to the people who have passed away so that they can re-unite with the Gods or with the ancestors. This article compares these two ceremonies to reveal the similar aspects.